Implementasi Literacy Camp dalam Meningkatkan Hasil AKM Siswa Kelas V SD Negeri Geritan - Junita Dwi Fransiska; Moh Farizqo Irvan (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This study aims to analyze the implementation of the Literacy Camp program in improving the Minimum Competency Assessment results of grade V students at SDN Geritan, Pati District, Central Java. The background of this study is based on the low literacy and numeracy skills of students, as indicated by the pre-test results, which showed 70% for literacy and 43% for numeracy. The Literacy Camp program was designed as a strategic intervention involving various creative and interactive learning activities, including reading sessions, educational games, and group discussions. This study employed a qualitative approach with descriptive methods, involving 28 Grade V students as research subjects. Data were collected through interviews, observation, documentation, and pre-test and post-test. The results showed that after participating in the Literacy Camp program, there was a significant increase in students' minimum competency assessment results. Specifically, the percentage of students able to answer literacy questions correctly increased to 77%, and the percentage of students able to answer numeracy questions correctly rose to 72%. These findings suggest that the Literacy Camp program is effective in enhancing students' literacy and numeracy skills while also offering a fun and engaging learning experience. This study is expected to serve as a reference for the development of similar programs in other schools to improve the quality of basic education in Indonesia.